(3GdLGeY aj GdCOhjI GdeaQOIs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s
(3ChdgG (B:s
(3eHJhQI GdChd , hChd GdehLhO efgG ef CKfGA MQa GdZjf bhdg(B: (3dCfg jLeO GddHf eKd eG JLeOg dCfaMI, hgh fHGJ dg hQb hbVjH ZGdSjfS (B: (3ZGeJfG HGdCfOdS JSejI HGdMedM hGgd eUQ jYQahfg HGdeKdKI s
(3BNQgG (B:s
(3jfeI CHh GdYHGS GdfHGJi(B: (3GdjfeI eYQhaI HGdbjQhGf hgj YfOge eNJHQI ai GdLQGMGJ hGddg CYde s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B75 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdWHs